Influence of Ti doping on the performance of a ZnO-based photodetector. (13th February 2017) - Nurfani, E; Zuhairah, N; Kurniawan, R; Muhammady, S; Sutjahja, I M; Winata, T; Darma, Y
Abstract: We study the influence of Ti doping on the photodetection properties of zinc oxide (ZnO) thin films. The pure ZnO and ZnO:3%Ti (TZO) films were deposited on Si substrates by using DC-unbalanced magnetron sputtering. From the scanning electron microscopy (SEM) images, the TZO film grows more homogeneously in comparison with the pure ZnO structure. We suggest that Ti dopants play a role in uniformly distributing ZnO elements from the sputtering target to the Si substrate. The transmittance spectra of the Fourier transform infrared spectroscopy show a peak splitting of Zn–O stretching in the TZO film, which is also related to the dopant-modified film morphology. X-ray diffraction (XRD) spectra show that the Ti dopants also change the main ZnO crystal orientation from (0 0 2) to (1 0 3). The ZnO and TZO film-based photodetectors were fabricated by using a metal–semiconductor–metal planar configuration with Ag as the metal contact. Based on the I–V characteristics, Ti doping in the ZnO system reduces the dark current and induces the enhancement of the photo-to-dark-current ratio. Our study shows the important role of Ti doping on the improvement of photodetection performance.